Structural Behaviour of Strengthened High-Performance Concrete-Filled Double Skin Steel Tube Beams - Nikbakht, E. (Springer, 2020)
Recently, the use of concrete-filled steel tube (CFST) composite beams has increased in the modern structural projects. In this study, the bending behaviour of high performance concrete-filled double skin tube (HPCFDST) strengthened with different CFRP layers is investigated. Mechanical properties of the incorporated high-performance self-compacting concrete are investigated. The structural performance of HPCFDST beam without CFRP layer as the control beam is compared with the HPCFDST beams strengthened with two and three layers of CFRP. The results show that the beam with CFRP sheets exhibited 19 greater load carrying capacity compared to the control beam. The beam with three layers of CFRP showed approximately similar strength, however, it exhibited greater ductility and deformation capacity compared to the beam with two layers of CFRP. Â© Springer Nature Singapore Pte Ltd 2020.